Prevalence of cigarette use in İstanbul - Ögel, Kültegin; Tamar, Defne; Özmen, Erol; Aker, Tamer; Sağduyu, Afşin; Boratav, Cumhur; Liman, Olcay (Journal of Dependence, 2003)
Objective: Most of the researches on the prevalence of cigarette smoking have been done among adolescent. In this research our objective was to determine the prevalence of cigarette smoking and accompanying socio-demographic characteristics among general population in İstanbul sample.Method: The research was conducted at June 2000 among 707 adults who live in 24 different districts of İstanbul. The respondents were interviewed face to face at their homes.Results: %76.9 of the sample reported that they smoked cigarette at least once in their lives. The prevalence of cigarette use was four times greater in males than females. Average age for smoking cigarette for the first time was 16,9 ± 5.4 years and %60.3 of respondents reported that they were regularly smoking cigarette. The highest prevelence for smoking cigarette regularly were found in the 26-35 age group. There were no significant differences among these regarding educational background, economic status and marital status. %79.4 of the respondents who smoked more than 10 cigarettes per day were also drinking alcohol more than twice a week or drinking everyday.Conclusion: In our research we found out that the prevalence of smoking regularly was higher among males and the age to start smoking was earlier among them. The highest ratio for smoking regularly were found in 26-35 age group.
Keywords: Cigarette smoking; prevalence; epidemiology; incidence; nicotine; addiction